2018
DOI: 10.1002/btpr.2600
|View full text |Cite
|
Sign up to set email alerts
|

Online measurement of the respiratory activity in shake flasks enables the identification of cultivation phases and patterns indicating recombinant protein production in various Escherichia coli host strains

Abstract: Escherichia coli is commonly used for recombinant protein production with many available host strains. Screening experiments are often performed in batch mode using shake flasks and evaluating only the final product concentration. This conventional approach carries the risk of missing the best strain due to limited monitoring capabilities. Thus, this study focuses on investigating the general suitability of online respiration measurement for selecting expression hosts for heterologous protein production. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
1
12
0
1
Order By: Relevance
“…An equivalent behavior is shown here for the first time in a mineral medium using arabinose as inducer. The reason for this observation (more or less constant OTR after induction) remains unclear and was observed for a single amino‐acid exchange, different host strains expressing the same product as well as a single nucleotide exchange . In all cases, biomass formation declined upon induction, which is in agreement with data from literature and a result of a higher ATP demand .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…An equivalent behavior is shown here for the first time in a mineral medium using arabinose as inducer. The reason for this observation (more or less constant OTR after induction) remains unclear and was observed for a single amino‐acid exchange, different host strains expressing the same product as well as a single nucleotide exchange . In all cases, biomass formation declined upon induction, which is in agreement with data from literature and a result of a higher ATP demand .…”
Section: Resultssupporting
confidence: 89%
“…The phenomenon of a more or less constant OTR after induction is well known from auto‐induction media containing glucose, lactose, and glycerol. Several studies identified a phase of rather constant OTR after induction with IPTG or its analogue lactose as production phase and indication of the strength of metabolic burden . An equivalent behavior is shown here for the first time in a mineral medium using arabinose as inducer.…”
Section: Resultsmentioning
confidence: 54%
“…This increase continues after induction, indicating no strong metabolic burden. Typically, a strong metabolic burden is reflected by visible changes in the OTR after induction (Rahmen et al, 2015a,b;Ihling et al, 2018;Mühlmann et al, 2018). The maximum oxygen transfer capacity (OTRmax) under the chosen cultivation conditions was determined to be 52 mmol/L/h according to Meier et al (2016).…”
Section: Early Induction Leads To Higher Productivitymentioning
confidence: 99%
“…As a new and promising tool to clarify auxotrophic deficiencies, the respiration activity monitoring system (RAMOS), based on shake flasks [ 20 , 21 ] and a recently developed system for 48-well microtiter plates (µRAMOS) using the same working principle was applied [ 22 ]. Numerous successful applications of the RAMOS device have already been published such as the detection of protein production [ 23 , 24 ], testing of yeast extract quality [ 5 ], evaluation of cellulose digestibility [ 25 ] and determination of polymer biocompatibility [ 26 ]. The RAMOS technology allows an online measurement of the oxygen transfer rate (OTR) during the entire cultivation time.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of optical density, OTR offers important information about the metabolic state of the culture [ 27 ]. Moreover, the OTR gives information about carbon source consumption and biomass formation [ 24 ]. In addition, limitations of a second substrate are easily detected.…”
Section: Introductionmentioning
confidence: 99%